2011
DOI: 10.1111/j.1365-2044.2011.06826.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical incident reports concerning anaesthetic equipment: analysis of the UK National Reporting and Learning System (NRLS) data from 2006-2008*

Abstract: Summary Anaesthetic equipment plays a central role in anaesthetic practice but brings the potential for malfunction or misuse. We aimed to explore the national picture by reviewing patient safety incidents relating to anaesthetic equipment from the National Reporting and Learning System for England and Wales between 2006 and 2008. We searched the database using the system’s own classification and by scrutinising the free text of relevant incidents. There were 1029 relevant incidents. Of these, 410 (39.8%) conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…The most common locations of a leak are the low pressure system, breathing system, or around endotracheal tube [3].…”
Section: Discussionmentioning
confidence: 99%
“…The most common locations of a leak are the low pressure system, breathing system, or around endotracheal tube [3].…”
Section: Discussionmentioning
confidence: 99%
“…Fasting and Gisvold (2002) suggested that 25% of equipment problems could be related to human error and furthermore that 18 of 29 cases were related to inadequate pre-use checks. Cassidy et al (2011) argued that it may be easier for a clinician to blame the equipment rather than to admit a misunderstanding or mistake. A 'human factors' approach (Reason 1990) can be utilised to focus on the organisational factors that led to the incident which occurred, rather than zoning individual blame (Mahajan 2010).…”
Section: Background To the Incidentmentioning
confidence: 99%
“…The factors included an inadequate skill mix and the competency of staff, including the specialist anaesthetic nurse who had to troubleshoot technical issues with the anaesthetic equipment. Cassidy et al (2011) drew attention to the National Patient Safety Agency (NPSA) which since 2006 has worked closely with clinicians in an attempt to extract useful lessons from incidents and to translate them into improvements in clinical practice. Since April 2016 a National Reporting and Learning System (NRLS) in the UK has been under the umbrella of NHS Improvement.…”
Section: Background To the Incidentmentioning
confidence: 99%
See 1 more Smart Citation
“…Since various independent sensors are used, the total gas concentration may differ from 100 vol.% e.g. if one sensor is miscalibrated, this can lead to conflicting information increasing the potential for a wrong decision of the caregiver [7,8]. A further disadvantage of conventional systems is the need for treatment of the gas sample like e.g.…”
Section: Introductionmentioning
confidence: 99%